Vergil's Political Commentary in the Eclogues, Georgics and Aeneid - Weeda, Leendert (De Gruyter, 2015)
In the book titled Vergil's political commentary in Eclogues, Georgics and Aeneid, the author examines Vergil's political views by analyzing the whole of the poet's work. He introduces the notion of the functional model suggesting that the poet often used this instrument when making a political statement. New interpretations of a number of the Eclogues and passages of the Georgics and the Aeneid are suggested and the author concludes that Vergil's political engagement is visible in much of his work. During his whole career the poet was consistent in his views on several major political themes. These varied from, the distress caused by the violation of the countryside during and after the expropriations in the 40s B.C., to the horrors of the civil war and the violence of war in general, and the necessity of strong leadership. Vergil hoped and expected that Octavian would establish peace and order, and he supported a form of hereditary kingship for which he considered Octavian a suitable candidate. He held Cleopatra in high regard, and he appreciated a more meaningful role for women in society. Vergil wrote poetry that supported Augustus, but he had also the courage to criticize Octavian and his policies. He was a commentator with an independent mind and was not a member of Augustus' putative propaganda machine.